Are older adults living with HIV more susceptible to omicron infection compared to their HIV-negative peers in China: a cross-sectional study - Yang, Jianhui; Strodl, Esben; Xu, Hong; Jiang, Haibo; Chu, Kun; Tan, Shiwen; Ye, Zehao; Shi, Hongbo; Chen, Weiqing; Tong, Feng (Frontiers in Public Health, 2025)
BackgroundOlder individuals are particularly susceptible to Omicron infection and long viral shedding durations. However, the associations between human immunodeficiency virus (HIV) status in older people, Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) infection, and viral shedding duration have not been determined. Therefore, this study aims to evaluate the impact of HIV infection status on Omicron infection rates and viral shedding duration in older people.MethodsThis was a cross-sectional study of older adults Chinese participants (aged ≥60 years) who were either people living with HIV (PLWH) or not infected with HIV. A total of 606 participants completed the questionnaire: 226 participants were diagnosed with HIV, and 380 participants reported being HIV-negative. Propensity score matching (PSM) was performed to balance the baseline parameters of the two groups and to exclude the effect of confounding variables, resulting in a final sample of 198 PLWH and 198 HIV-negative participants for data analysis. Risk or protective factors for Omicron infection and a long viral shedding duration, including demographics, HIV-related factors, and comorbidities, were investigated using multivariable logistic regression.ResultsThe risk of SARS-CoV-2 infection in the PLWH group was lower than that in the HIV-negative group (odds ratio [OR] = 0.455 [0.285–0.724]). However, PLWH experienced a longer viral shedding duration than the comparison group after Omicron infection (OR = 2.303 [1.221, 4.346]). In addition, older adults with diabetes had higher odds of experiencing a longer viral shedding duration than those without diabetes (OR = 2.742 [1.262, 5.957]). PLWH who had diabetes were at a higher risk of longer viral shedding duration compared with the HIV-negative group (OR = 2.232 [1.132, 4.400]).ConclusionOur study demonstrated that older PLWH have decreased odds of being infected with Omicron and experience longer viral shedding duration in comparison to matched HIV-negative controls. Furthermore, diabetes may prolong SARS-CoV-2 viral shedding duration in older people. Targeted monitoring and intervention should be implemented among vulnerable groups, such as older adults individuals infected with HIV or those with underlying diabetes, to prevent and respond to potential outbreaks of SARS-CoV-2 in the future.